Interface‐Assisted Sign Inversion of Magnetoresistance in Spin Valves Based on Novel Lanthanide Quinoline Molecules. (23rd October 2017) - Bedoya‐Pinto, Amilcar; Miralles, Sara G.; Vélez, Saül; Atxabal, Ainhoa; Gargiani, Pierluigi; Valvidares, Manuel; Casanova, Fèlix; Coronado, Eugenio; Hueso, Luis E.
Abstract: Molecules are proposed to be an efficient medium to host spin‐polarized carriers, due to their weak spin relaxation mechanisms. While relatively long spin lifetimes are measured in molecular devices, the most promising route toward device functionalization is to use the chemical versatility of molecules to achieve a deterministic control and manipulation of the electron spin. Here, by combining magnetotransport experiments with element‐specific X‐ray absorption spectroscopy, this study shows the ability of molecules to modify spin‐dependent properties at the interface level via metal–molecule hybridization pathways. In particular, it is described how the formation of hybrid states determines the spin polarization at the relevant spin valve interfaces, allowing the control of macroscopic device parameters such as the sign and magnitude of the magnetoresistance. These results consolidate the application of the spinterface concept in a fully functional device platform. Abstract : Molecular spin valves based on novel lanthanoid quinolines are presented. Combining magnetotransport and in situ X‐ray absorption spectroscopy, this study demonstrates that specific metal‐molecule hybrid states govern the interface spin polarization and hence control the sign and magnitude of the device magnetoresistance. This work consolidates the spinterface concept for driving macroscopic output device parameters in a fully functional spintronic device.